Construction of Malayan Zapin after Covid-19 Pandemic - Robby Hidajat; Muhammad ‘Afaf Hasyimy; Ni Wayan Mudiasih (Institut Seni Indonesia Denpasar, 2023)
Purpose: the research reviews the recent condition of Malayan Zapin dance in various regions in Indonesia, including Palembang, Riau, Banjarmasin, Gresik, and Tarakan. These regions are places where Malayan Zapin dance are redesigned for entertainment. Although the conserver societies are not quite wealthy, their existence is not extinct despite the outbreak of Covid-19 pandemic for two years. The objective of this research is therefore to understand the construction of Zapin dance from Malay ethnic in several conservation regions. Methods: The method of this research is using qualitative descriptive approach. Data concerning Zapin development are collected by conducting virtual interview with key informants through Whatsapp, Zoom and video call. Data analysis procedure involves collecting, sorting, and tabulating the data. Analysis technique is interpretative descriptive. Result and discussion: The results of this research show that (1) Zapin is constructed as the complement to local ethnic dances, (2) Zapin is constructed as the alternative dance material to be taught at school, and (3) Zapin is constructed a creative work. Implication: The authors find that the effort of the conserver societies to develop Zapin dance as a remarkable topic and the development of Zapin dance as a genuine art of Indonesian archipelago are barely studied.